2021
DOI: 10.1002/pbc.29168
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role and clinical implications of proteasome inhibition in medulloblastoma

Abstract: Ubiquitin proteasome-mediated protein degradation has been implicated in posttranslational oncogenesis in medulloblastoma. Current research is evaluating the clinical implications of proteasome inhibition as a therapeutic target. In medulloblastoma cell lines, proteasome inhibitors induce apoptosis and inhibit cell proliferation via multiple pathways involving activation of caspase pathways, NFκB (nuclear factor kappalightchain-enhancer of activated B cells) pathway inhibition, reduced AKT/mTOR pathway activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
(144 reference statements)
0
1
0
Order By: Relevance
“…In line with this, it has been demonstrated that bortezomib, a proteasome inhibitor, which was previously found to selectively kill MB cells, induces cell death in a ROS-dependent manner ( Ohshima-Hosoyama et al, 2011 ). Bortezomib treatment results in the stabilization of NOXA, a member of the Bcl-2 family, triggering apoptosis in response to high ROS levels in a p53-independent manner ( Ohshima-Hosoyama et al, 2011 ; Hoerig et al, 2021 ). A recent molecular work from Li et al, has studied the effects of Liposomal Honokiol (Lip-HNK), a small bisphenol lignin delivered into liposomes, as a potential treatment against MB ( Li et al, 2022 ).…”
Section: Metabolic Reprogramming In Medulloblastomamentioning
confidence: 99%
“…In line with this, it has been demonstrated that bortezomib, a proteasome inhibitor, which was previously found to selectively kill MB cells, induces cell death in a ROS-dependent manner ( Ohshima-Hosoyama et al, 2011 ). Bortezomib treatment results in the stabilization of NOXA, a member of the Bcl-2 family, triggering apoptosis in response to high ROS levels in a p53-independent manner ( Ohshima-Hosoyama et al, 2011 ; Hoerig et al, 2021 ). A recent molecular work from Li et al, has studied the effects of Liposomal Honokiol (Lip-HNK), a small bisphenol lignin delivered into liposomes, as a potential treatment against MB ( Li et al, 2022 ).…”
Section: Metabolic Reprogramming In Medulloblastomamentioning
confidence: 99%